2019
DOI: 10.1039/c8ce02050g
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Ti3C2 and MOF-derived CoSx boosting the photocatalytic hydrogen production activity of TiO2

Abstract: We report a novel TiO2 nanocrystals photocatalyst confined by ZIF-67-templated porous CoSx, with conductive Ti3C2 boosting the transport efficiency of the charge carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…57,195 Apart from acting as TM oxide precursors, MXenes can also serve as efficient PC/PEC HER co-catalysts themselves to promote photo-generated charge carrier separation when coupled to semiconductors. 133,[196][197][198][199] The most widely studied MXene, Ti3C2Tx, has been applied as a PC HER co-catalyst and successfully coupled to a variety of semiconducting photocatalysts such as TM oxides, 191,196 sulfides, 124,187 perovskites, 197,198 and g-C3N4. 133,199 For instance, Ran et al investigated the use of Ti3C2Tx as a HER co-catalyst, with CdS acting as a photo-absorber for PC HER.…”
Section: Mxene Hybrids and Composites For Electrocatalytic (Ec) Oer And Water Splittingmentioning
confidence: 99%
See 2 more Smart Citations
“…57,195 Apart from acting as TM oxide precursors, MXenes can also serve as efficient PC/PEC HER co-catalysts themselves to promote photo-generated charge carrier separation when coupled to semiconductors. 133,[196][197][198][199] The most widely studied MXene, Ti3C2Tx, has been applied as a PC HER co-catalyst and successfully coupled to a variety of semiconducting photocatalysts such as TM oxides, 191,196 sulfides, 124,187 perovskites, 197,198 and g-C3N4. 133,199 For instance, Ran et al investigated the use of Ti3C2Tx as a HER co-catalyst, with CdS acting as a photo-absorber for PC HER.…”
Section: Mxene Hybrids and Composites For Electrocatalytic (Ec) Oer And Water Splittingmentioning
confidence: 99%
“…Thereafter, anionic precursors are introduced to chemically react and form the desired secondary materials on the MXene surface. An additional annealing step is usually required to complete the reaction and enhance the integration of the secondary material on MXenes. A variety of inorganic materials such as TM oxides, phosphides, chalcogenides, nitrides, MOFs, perovskites, and LDHs , have been hybridized with MXenes this way (Figure ). Yu et al prepared FeNi-LDH@Ti 3 C 2 T x hybrids by the coprecipitation of Fe 3+ and Ni 2+ cations on negatively charged Ti 3 C 2 T x sheets for EC OER (Figure b) .…”
Section: Design Strategies For Mxene Hybrids and Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most attractive properties of MXenes is the high electrical conductivity, which is also the most commonly utilized feature of MXenes to accept and transport photogenerated electrons for improving the activities of photocatalysts. [81,97,117,121,200,201] As the research and understanding on the electronic properties of MXenes go deeper, the electronic structure of MXenes has been found to be quite tunable. [50] The theoretical works have demonstrated that the work function/ Fermi level of MXenes critically depends on the surface terminated groups.…”
Section: Electronic Structure Mutability Of Mxenesmentioning
confidence: 99%
“…The direct conversion of sustainable solar power into ecofriendly energy over high performance photocatalysts has been extremely signicant for powering human society. [1][2][3][4][5][6][7] Up to now, it is universally recognized that the serious recombination, underutilization and poor transport of photon-generated carriers weaken the photocatalytic activity of the photocatalyst. [8][9][10][11][12] Consequently, extensive efforts have been devoted to constructing heterostructures or phase junctions, which could increase the specic surface area of the photocatalyst, 2, [13][14][15][16][17][18][19][20][21] and adopting a suitable cocatalyst for improving the separation, transport and utilization of the photo-induced charge carriers.…”
Section: Introductionmentioning
confidence: 99%